Reductive Otoplasty and Facial Debulking in a Pediatric Patient With PIK3CA-Related Overgrowth. (December 2021) - Das, Rishub K.; Rahman, Barry G.; Phillips, James D.; Borst, Alexandra J.; Jaeger, Nolan; Golinko, Michael S.
Overgrowth syndromes encompass a number of rare genetic diseases with heterogeneous clinical phenotypes. Accordingly, there is a strong imperative to collect data and classify these disorders to aid in diagnosis and management. Recent advances in the genetics of overgrowth syndromes have identified mutations in the PIK3CA gene. These somatic mutations manifest in progressive segmental overgrowth of fibrous and adipose tissue and bone, vascular malformations, and in some cases, increased risk for malignancy. Targeted medical therapy is under investigation for the management of PROS, but treatment of overgrowth relies on surgical debulking. Macrotia in PIK3CA- related overgrowth spectrum (PROS) has not been reported in the literature. In this case, we discuss a novel approach to reductive otoplasty and facial soft tissue debulking in a pediatric patient with PROS.